Comportamiento agronómico y productivo de la línea promisoria de arroz (Oryza sp.) L-17 cultivada en la zona de Puebloviejo, Provincia Los Ríos - Cherrez Baquerizo, Jean Pool (2025)
In Ecuador, rice (Oryza sativa L.) is essential for the diet of a large part of its population; this is because it contains starch, proteins, and several vitamins. This study aimed to evaluate the agronomic and productive performance of the promising rice line L-17 compared to the commercial variety SFL-11 in the Pueblo Viejo area, Los Ríos province. The research was carried out on a farm owned by Mr. Ángel Miguel Olivo Coello, located in the Pueblo Viejo area at the geographic coordinates 790 32 00 "West longitude and 010 33 00" South latitude; with an elevation of 14 meters above sea level, with a total population of 148 seedlings in three replications (R1, R2 and R3) within 4 m² plots. Both the L-17 line and the commercial variety were evaluated with 58 seedlings in each replication. A nonparametric statistical approach using Kruskal-Wallis analysis was applied, examining essential factors such as plant count per hectare, planting spacing, height, tiller count, panicle count, panicle length, total grain count, 1,000-grain weight, and hulled and unhulled grain measurements, as well as total yield in kg/ha. The promising L-17 line showed advantages in terms of profitability, with a higher net profit and a superior benefit/cost ratio (2,003 versus 1,756 for the commercial variety). Although the SFL-11 variety showed better values in plant height, tiller count, and 1,000-grain weight, the L-17 line stood out in its adaptation and productivity, consolidating itself as a viable alternative for rice producers in the region. It is concluded that the promising rice line L-17 had very good grononomic performance and was very early in its vegetative cycle in the field in the area of Pueblo Viejo, Los Ríos province; the commercial variety SFL-11 showed better results in distance between plants and rows, as well as in plant height